The search for new physics in the diphoton decay channel and the upgrade of the Tile-Calorimeter electronics of the ATLAS detector - Reed, Robert Graham (My University, 2017)
The discovery of the Higgs boson at the Large Hadron Collider in Switzerland marks the beginning of a new era: Physics beyond the Standard Model (SM). A model is proposed to describe numerous Run I features observed with both the ATLAS and CMS experiments. The model introduces a heavy scalar estimated to be around 270 GeV and an intermediate scalar which can decay into both dark matter and SM particles. Three diﬀerent ﬁnal state searches, linked by the new hypothesis, are presented. These are the hh → γγb¯ b, γγ + Emiss T and high mass diphoton channels. No signiﬁcant excesses were observed in any channel using the available datasets and limits were set on the relevant cross sections times branching ratios. The lack of statistics in the γγb¯ b analysis prevents any conclusive statement in regard to the excess observed with Run I data. Observing no excess in the γγ + Emiss T channel with the current amount of data is also consistent with the intermediate scalar decaying to SM particles. This could explain the excess of Higgs bosons produced in associations with top quarks in the multilepton ﬁnal states observed in ATLAS and CMS in Run I and Run II. The work presented provides a deeper understanding on the underlying phenomenology of the hypothesis and provides a foundation for future work. The ATLAS detector underwent a stringent consolidation and validation eﬀort before data taking could commence in 2015. A high voltage board was designed and implemented into a portable test-bench used in the certiﬁcation and validation process. In addition to these eﬀorts, the electronics on the ATLAS detector are being improved for the Phase-II upgrade program in 2024. A software tool has been designed which integrates the envisioned Phase-II backend infrastructure into the existing ATLAS detector control system. This software is now an ATLAS wide common tool used by multiple sub-detectors in the community.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy, School of Physics. Johannesburg. February, 2017
Keywords: Particles (Nuclear physics); Particle accelerators; Large Hadron Collider (France and Switzerland)